2002
DOI: 10.1038/sj.onc.1205894
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated expression of antisense MMP-9 in glioma cells inhibits tumor growth and invasion

Abstract: Matrix metalloproteinase 9 (MMP-9) is known to play a major role in cell migration and invasion in both physiological and pathological processes. Our previous work has shown that increased MMP-9 levels are associated with human glioma tumor progression. In this study, we evaluated the ability of an adenovirus containing a 528 bp cDNA sequence in antisense orientation to the 5' end of the human MMP-9 gene (Ad-MMP-9AS) to inhibit the invasiveness and migratory capacity of the human glioblastoma cell line SBN19 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 41 publications
3
68
0
Order By: Relevance
“…In the present study, we directly exposed LN229 cells to exogenous human purified MMP-9, and showed that MMP-9 acts as a stimulator of both astrocytoma cell growth and motility. Similar results were indirectly reported by Lakka et al (2002), who showed that the downregulation of MMP-9 expression reduced astrocytoma cell growth, motility, and invasion. In addition to direct MMP-9-induced stimulation of cell growth and motility, we showed that the proteolysis of the IGFBP2-IGFII complex by MMP-9 caused a dramatic increase in both cell growth and cell motility, suggesting that MMP-9 and the IGF system may collaborate to promote astrocytoma aggressiveness.…”
Section: Discussionsupporting
confidence: 89%
“…In the present study, we directly exposed LN229 cells to exogenous human purified MMP-9, and showed that MMP-9 acts as a stimulator of both astrocytoma cell growth and motility. Similar results were indirectly reported by Lakka et al (2002), who showed that the downregulation of MMP-9 expression reduced astrocytoma cell growth, motility, and invasion. In addition to direct MMP-9-induced stimulation of cell growth and motility, we showed that the proteolysis of the IGFBP2-IGFII complex by MMP-9 caused a dramatic increase in both cell growth and cell motility, suggesting that MMP-9 and the IGF system may collaborate to promote astrocytoma aggressiveness.…”
Section: Discussionsupporting
confidence: 89%
“…Although its role in metastatic tumor cell growth is still unclear, increased MMP expression is frequently accompanied by tumor metastasis and suppression of MMP expression could be used as a growth inhibitory treatment to prevent tumor metastasis. 23,27,28 When pshHIF-1a was administered to tumor-bearing mice by the hydrodynamics-based procedure, a significant reduction in the number of tumor cells was observed (Figure 6a). This result indicates that HIF-1a expression in either tumor cells or hepatic normal cells or in both types of cells plays an important role in tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…MMP-2, but not MMP-9 was found to be necessary for glomerular mesangial cell proliferation and differentiation (Turck et al, 1996). Similarly, adenoviral delivery of antisense mRNA of MMP-9 effectively suppressed tumor xenograft growth in vivo (Lakka et al, 2002). Small interfering RNAs have also been used to specifically silence MMP-9.…”
Section: Synthetic Gelatinase Inhibitorsmentioning
confidence: 99%